2010
DOI: 10.1017/s0007114510004708
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metabolic syndrome and immunostimulant activities of Egyptian fenugreek seeds in diabetic/obese and immunosuppressive rat models

Abstract: Preliminary trials have suggested possible hypoglycaemic, hypolipidaemic and immunomodulatory properties of the fenugreek plant. Here, we evaluated and compared the efficacy of Egyptian fenugreek seed powder (FSP, 0·5 and 1·0 g/kg body weight) in alleviating the experimentally induced metabolic syndrome (in type 1 diabetic and obese rat models) and experimentally induced immunosuppression and delay in burn-healing (in cyclophosphamide (CP)-treated rats). FSP significantly alleviated (P,0·05-0·001) most signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Previous studies in alloxan or streptozotocin-induced diabetic rats, rabbits and normal mice or glucose-infused rats found similar effects on plasma glucose (Ajabnoor and Tilmisany, 1988;Ali et al, 1995;Khosla et al, 1995;Abdel-Barry et al, 1997;Zia et al, 2001;Vats et al, 2002;Vijayakumar et al, 2005;Gad et al, 2006;Hannan et al, 2007;Xue et al, 2007;Mowla et al, 2009;Moorthy et al, 2010a, b;Yadav et al, 2010;Ramadan et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies in alloxan or streptozotocin-induced diabetic rats, rabbits and normal mice or glucose-infused rats found similar effects on plasma glucose (Ajabnoor and Tilmisany, 1988;Ali et al, 1995;Khosla et al, 1995;Abdel-Barry et al, 1997;Zia et al, 2001;Vats et al, 2002;Vijayakumar et al, 2005;Gad et al, 2006;Hannan et al, 2007;Xue et al, 2007;Mowla et al, 2009;Moorthy et al, 2010a, b;Yadav et al, 2010;Ramadan et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
“…Saponins, such as diosgenin contained in fenugreek, form large micells from bile acid and saponin molecules in the small intestine, and these micelles inhibit the cholesterol absorption by directly excreting cholesterol in feces [15,16]. Diosgenin also reduces the triglyceride content and mRNA expression levels of lipogenic genes (FAS, SCD-1 and ACC) and suppresses LXRα transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In a manner similar to glucose metabolism, lipid parameters seem to be positively influenced by the administration of all sixteen different legumes that have been included in this review. Among the most widely mentioned beneficial improvements, the reduction of different lipid fractions in plasma, such as total-, LDL-, HDL-cholesterol and TAG (20,22,(28)(29)(30)(31)34,36,38,46,48,(54)(55)(56)58,61) , hepatic TAG and phospholipid content (17,19,60) , or both of them (18,24,(40)(41)(42)(43)45,52,61) , is reported. Other improvements associated with lipid metabolism and body composition are the decrease of body fat mass and white adipose tissue by Glycine max (17,25) , as well as the reduction of hepatic steatosis induced by this same legume (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Srichamroen et al (35) demonstrated that galactomannan of fenugreek reveals its function at the intestinal level by reducing the in vitro uptake of glucose in both jejunum and ileal segments. Moreover, the hypolipidaemic properties of fenugreek are clearly demonstrated by lower levels of lipid fractions in blood (28)(29)(30)(31)34) and TAG in epidydimal adipose tissue (34) , the weight of the latter being significantly lower after combining high-fat diets with powder of fenugreek seeds (28) . Liver function markers such as alanine transaminase (ALT), aspartate transaminase (AST) and alkaline phosphatase activities (29,31) , concentration of TBARS, as well as the activities of antioxidant enzymes such as catalase and superoxide dismutase (25) , decreased because of the administration of this legume.…”
Section: Trigonella Foenum Gracecum/fenugreekmentioning
confidence: 99%